Analytic psychology - Stout, George Frederick, 1860-1944 (London : Allen & Unwin ; New York : Macmillan, 1918)
"The present work aims to bring systematic order into the crowd of facts concerning our mental life revealed by analysis of ordinary experience. Psychology is the most empirical of the sciences; and of all the branches of Psychology what is commonly though inaccurately called the introspective is most immersed in matter-of-fact. Its function is to describe, analyse, and arrange. In this respect it is contrasted with what is called the Genetic or Synthetic Method, which instead of attempting merely to ascertain and define the processes of the developed consciousness, proposes to itself the task of tracing the evolution of mind from its lowest to its highest planes. When I first planned the present work, I found myself baffled in the attempt to follow the genetic order of treatment without a preparatory analysis of the developed consciousness. Our knowledge of mental processes, as we can observe and infer them in our own ordinary experience, is essential as a clue to the nature of mental process at lower levels. I therefore found myself driven to pave the way for genetic treatment by a previous analytic investigation; and the result was the present work. Chapters VIII., IX., X., and XI. in book II have already appeared as articles in the pages of Mind. They have in each instance been greatly expanded and altered, so that they may be considered as virtually new. The general Introduction is an expansion and modification of a paper printed in the Proceedings of the Aristotelian Society on "The Scope and Method of Psychology". The chapter on "Relative Suggestion" appeared in the Proceedings of the Society for 1895"
Vol. 2
Keywords: Psychology; Psychology